Inhaled nitric oxide for neonates with persistent pulmonary hypertension of the newborn in the CINRGI study: time to treatment response - Leif D. Nelin; Jim L. Potenziano (BMC, 2019)
Abstract Background Substantial numbers of neonates with hypoxic respiratory failure (HRF) do not immediately respond to inhaled nitric oxide (iNO) and are often labeled as non-responders. This retrospective data analysis assessed time to treatment response in the iNO key registration trial. Methods Treatment response was defined as a ≥10% increase in partial pressure of arterial oxygen (PaO2) or a ≥10% decrease in oxygenation index (OI) after initiation of study gas without the need for extracorporeal membrane oxygenation (ECMO). The proportion of patients showing a response at 30 min, 1 h, 24 h, and >24 h after iNO or placebo initiation was calculated and stratified by baseline PaO2 and OI. Results Data from 248 patients (iNO: n = 126; placebo: n = 122) were included; 66 patients receiving iNO showed improvement in oxygenation without needing ECMO versus 38 receiving placebo. Of the 66 iNO responders, 73% responded within ≤30 min, 9% within ≤1 h, 12% within ≤24 h, and 6% after 24 h. Of the 38 patients with improvement in oxygenation without needing ECMO while receiving placebo, 53% showed improvement within ≤30 min, 16% within ≤1 h, 29% within ≤24 h, and 3% after 24 h. Baseline disease severity was not predictive of time to response. Of the 48 patients in the iNO treatment group who were classified as non-responders due to eventual need for ECMO and not included in the analysis of responders, 40 (83%) had an initial improvement in oxygenation during iNO therapy. Conclusions Changes in PaO2 and OI after iNO initiation appear to be imprecise biomarkers of response to therapy in neonates with HRF. In some patients treated with iNO, it took up to 24 h to achieve improvement in oxygenation without need for ECMO, and a majority of those who eventually required ECMO did show an initial improvement in oxygenation during iNO treatment. Thus, reliable, objective, early criteria for iNO response still need to be established, and initial PaO2/OI responses should be interpreted with caution, particularly when considering discontinuing iNO therapy.